TELAAH HUKUM ISLAM TERHADAP FENOMENA JUDI ONLINE: PROBLEMATIKA, DAMPAK, DAN SOSIALNYA - Muh Yaumil Akhir; Nurul Qadriyyah. Ak; Delmi; M. Hasibuddin Mahmud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The phenomenon of online gambling has become a serious problem that plagues various circles of society, especially the younger generation. Technological advances exacerbate this condition because of the very easy and wide access. From the perspective of Islamic law, gambling or maysir is a forbidden act because it contains speculative and harmful elements. This article aims to examine Islamic law on the practice of online gambling, analyze the impact caused, and examine the social aspects of the phenomenon. This research uses a qualitative-descriptive method with a normative-theological approach. The results of the study show that online gambling is contrary to the principles of sharia, causing damage to the moral, economic and social order of society.